Acridine yellow G (AYG) as a photo-induced electron transfer (PET) photocatalyst employed for the radical Michael–Mannich cyclocondensation of imines - Mohamadpour, Farzaneh (Frontiers in Chemistry, 2022)
A four-component domino Michael-Mannich cyclocondensation of amines, dialkyl acetylenedicarboxylaes, and formaldehyde was utilized to lay out a green technique for sans metal combination of polyfunctionalized dihydro-2-oxypyrroles. Involving visible light as an environmentally friendly power source and acridine yellow G (AYG) as a Photo-induced electron transfer (PET) photocatalyst. The motivation behind this examination is to expand the utilization of a non-metal dye that is both reasonable and broadly accessible. Photochemically catalyzed AYG flaunts exceptional returns, energy effectiveness, and natural agreeableness, as well as extraordinary iota economy, efficient highlights, and comfort of purpose. Subsequently, many compound and natural factors can be followed over the course of time. Shockingly, gram-scale cyclization is conceivable, proposing that the strategy could be utilized in industry.